S100A4/TCF Complex Transcription Regulation Drives Epithelial-Mesenchymal Transition in Chronic Sinusitis Through Wnt/GSK-3β/β-Catenin Signaling - Gong, Ningyue; Shi, Lei; Bing, Xin; Li, Hui; Hu, Houyang; Zhang, Pan; Yang, Huiming; Guo, Na; Du, Hongjie; Xia, Ming; Liu, Chengcheng (Frontiers in Immunology, 2022)
Epithelial-mesenchymal transition (EMT) is thought to be involved in the tissue remodeling and long-term inflammatory process of chronic sinusitis (CRS), but the driving mechanism is still unclear. Using high-resolution mass spectrometry, we performed a proteomic screen of CRS nasal mucosal tissue to identify differentially expressed proteins. Data are available via ProteomeXchange with identifier PXD030884. Specifically, we identified S100 calcium binding protein A4 (S100A4), an effective factor in inflammation-related diseases, and its downstream protein closely related to tissue fibrosis collagen type I alpha 1 chain (COL1A1), which suggested its involvement in nasal mucosal tissue remodeling. In addition, stimulation of human nasal epithelial cells (HNEpCs) with lipopolysaccharide (LPS) mimicked the inflammatory environment of CRS and showed that S100A4 is involved in regulating EMT and thus accelerating tissue remodeling in the nasal mucosa, both in terms of increased cell motility and overexpression of mesenchymal-type proteins. Additionally, we further investigated the regulation mechanism of S100A4 involved in EMT in CRS. Our research results show that in the inflammatory environment of CRS nasal mucosal epithelial cells, TCF-4 will target to bind to S100A4 and regulate its transcription. The transcription of S100A4 in turn affects the execution of the important signaling pathway in EMT, the Wnt/GSK-3β/β-catenin pathway, through the TCF-4/β-catenin complex. In conclusion, this study confirmed that the expression of S100A4 was significantly increased during the progressive EMT process of CRS mucosal epithelial cells, and revealed that the transcriptional regulation of S100A4 plays an important role in the occurrence and development of EMT. This finding will help us to better understand the pathogenesis behind the remodeling in CRS patients, and identify target molecules for the treatment of CRS.